Evidence of spin-orbital angular momentum interactions in relativistic heavy-ion collisions - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Martin, Nicole Alice; Ohlson, Alice; Reygers, Klaus; et al. (Physical review letters, 2020)
The first evidence of spin alignment of vector mesons (K*0 and ϕ) in heavy-ion collisions at the Large Hadron Collider (LHC) is reported. The spin density matrix element ρ00 is measured at midrapidity (|y|<0.5) in Pb-Pb collisions at a center-of-mass energy (√sNN) of 2.76 TeV with the ALICE detector. ρ00 values are found to be less than 1/3 (1/3 implies no spin alignment) at low transverse momentum (pT<2 GeV/c) for K*0 and ϕ at a level of 3σ and 2σ, respectively. No significant spin alignment is observed for the K0S meson (spin=0) in Pb-Pb collisions and for the vector mesons in pp collisions. The measured spin alignment is unexpectedly large but qualitatively consistent with the expectation from models which attribute it to a polarization of quarks in the presence of angular momentum in heavy-ion collisions and a subsequent hadronization by the process of recombination.